Inguinal Herniation of the Urinary Bladder Presenting as Recurrent Urinary Retention. (17th May 2015) - Frenkel, Amit; Roy-Shapira, Aviel; Shelef, Ilan; Shaked, Gadi; Brotfain, Evgeni; Koyfman, Leonid; Borer, Abraham; Klein, Moti
Abstract : Herniation of the urinary bladder into the inguinal canal is an uncommon finding, observed in 0.5–4% of inguinal hernias (Curry (2000)). It is usually associated with other conditions that increase intra-abdominal pressure such as bladder neck obstruction due to prostatic hypertrophy. Consequently, in men, it is usually associated with some degree of urinary retention. We present a 42-year-old man in whom herniation of the urinary bladder was the cause of urinary retention, and not vice versa. The patient was on tumor necrosis factor alpha antagonist (TNFA) (Etanercept) for severe Ankylosing spondylitis. Initially, the urinary retention was thought to be a side effect of the medication, but after the drug was discontinued, urinary retention persisted. CT and MRI demonstrated huge herniation of the urinary bladder into the inguinal canal. Immediately after the hernia was repaired, bladder function was restored. TNF treatment was restarted, and no further urinary symptoms were observed in the next two years of follow-up. In this case, the primary illness and its treatment were distracting barriers to early diagnosis and treatment. In younger patients with a large hernia who develop unexpected urinary retention, herniation of the urinary bladder should be highly considered in the differential diagnosis.